2022
DOI: 10.3390/ijms23169418
|View full text |Cite
|
Sign up to set email alerts
|

Multiplexed Human Gene Expression Analysis Reveals a Central Role of the TLR/mTOR/PPARγ and NFkB Axes in Burn and Inhalation Injury-Induced Changes in Systemic Immunometabolism and Long-Term Patient Outcomes

Abstract: Burn patients are subject to significant acute immune and metabolic dysfunction. Concomitant inhalation injury increases mortality by 20%. In order to identify specific immune and metabolic signaling pathways in burn (B), inhalation (I), and combined burn-inhalation (BI) injury, unbiased nanoString multiplex technology was used to investigate gene expression within peripheral blood mononuclear cells (PBMCs) from burn patients, with and without inhalation injury. PBMCs were collected from 36 injured patients an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…A remarkable increase was observed in the midnight and noon expression of Nfe2l2 and Cxcl5 mRNA with pro‐inflammatory properties. NFκB axis has great importance for lung immunometabolism and injury (Mahung et al, 2022 ; Soto et al, 2020 ; Tang et al, 2018 ). NFκB through TNF‐alpha can stimulate cells to upregulate several pro‐inflammatory mediators such as neutrophilic chemokine CXCL5 (Kuret et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…A remarkable increase was observed in the midnight and noon expression of Nfe2l2 and Cxcl5 mRNA with pro‐inflammatory properties. NFκB axis has great importance for lung immunometabolism and injury (Mahung et al, 2022 ; Soto et al, 2020 ; Tang et al, 2018 ). NFκB through TNF‐alpha can stimulate cells to upregulate several pro‐inflammatory mediators such as neutrophilic chemokine CXCL5 (Kuret et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Downregulation of P70S6K after MSC-EV treatment compared to untreated mice also suggests that mTOR activation has been reduced ( 67 ). We have shown that the mTOR/PPARγ axis is partly responsible for the acute and chronic (analogous to DEARE) immune dysfunction in burn injury ( 68 70 ), and experiments are underway to determine if MSC-EV can modulate this response in an mTOR-dependent fashion. It is therefore tempting to speculate that a key component of the reprogramming capacity of MSC-EVs is mTOR dependent.…”
Section: Discussionmentioning
confidence: 99%